Unlawful prosecution in the case regarding the destruction of a forest eco-system - Denis Solodov; Elżbieta Zębek (Revista Brasileira de Direito Processual Penal)
The overall complexity of the subject matter and the required high level of expertise make environmental crime investigations quite a challenging task for law enforcement. The clandestine nature of environmental offences combined with the environmental law’s intricacy is among the reasons behind prosecutorial failures. The authors analyze a criminal case regarding illegal deforestation, which eventually ended up in an acquittal. By retracing the steps that led to wrongful prosecution and accusations in this criminal case, the authors reflect on some legal and practical challenges concerning environmental crime investigations in Europe and in Poland, including the problem of timely detection of environmental infringements, the use of proper evidence-gathering procedures, as well as the issues related to the methodology of environmental damage assessment. In this regard, the authors analyze the provisions of the Environmental Compliance Assurance Guidance “Combating environmental crimes and related infringements” adopted by the EU Commission in 2021.